The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/ieam.5630010401
|View full text |Cite
|
Sign up to set email alerts
|

The european union risk assessment on zinc and zinc compounds: The process and the facts

Abstract: A risk assessment on zinc and zinc compounds was carried out within the framework of Council Regulation 793/93/EEC on Existing Chemicals. This risk assessment basically followed the European Union (EU) technical guidance documents (TGDs). These TGDs are built on the current knowledge on quantitative risk assessments, mainly for organic chemicals. This article describes the tailor-made approach for the zinc risk assessment. This work lasted almost a decade and involved the contributions of all EU member states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(43 citation statements)
references
References 33 publications
(32 reference statements)
0
40
0
Order By: Relevance
“…Although controversial from the outset [31,32], the SSD approach has found wide application in metals risk assessment [17,33]. Take-up of the SSD approach for risk assessment was facilitated by a validation exercise that suggested that an HC 5 derived from the soil species toxicity database for Zn, provided the requisite level of protection for soil microbial functions (no effect on 95% of all functions) as measured by community physiological profiling using BIOLOG TM plates [34,35].…”
Section: Effects On Individuals Risk Assessment and The Prediction Omentioning
confidence: 99%
See 1 more Smart Citation
“…Although controversial from the outset [31,32], the SSD approach has found wide application in metals risk assessment [17,33]. Take-up of the SSD approach for risk assessment was facilitated by a validation exercise that suggested that an HC 5 derived from the soil species toxicity database for Zn, provided the requisite level of protection for soil microbial functions (no effect on 95% of all functions) as measured by community physiological profiling using BIOLOG TM plates [34,35].…”
Section: Effects On Individuals Risk Assessment and The Prediction Omentioning
confidence: 99%
“…A recent example of the use of SSDs in metals risk assessment under EU existing substance guidelines has been the assessment for Zn [33]. In this appraisal, a large volume of toxicity data was available from the literature and this was further augmented with data generated in a series of targeted studies.…”
Section: Effects On Individuals Risk Assessment and The Prediction Omentioning
confidence: 99%
“…Growth inhibition experiments revealed comparable toxicity for nanoparticulate ZnO, bulk ZnO, and ZnCl 2 , with a 72 h IC50 value around 60 µ g/l zinc, which was attributable solely to dissolved zinc. Consideration of published species sensitivity distributions (Bodar et al , 2005 ) indicates that 5 mg/l zinc is suffi cient to cause adverse effects to a majority of aquatic species, including algae, invertebrates and fi sh. Thus, the most likely cause of nano (or bulk) ZnO aquatic toxicity is via dissolution and not necessarily through any specifi c particulate effects.…”
Section: Release Of Toxic Dissolved Speciesmentioning
confidence: 99%
“…Although zinc is an essential element at trace concentrations and used not only for industries such as metal plating but also for personal care products, chronic toxicity for specific aquatic organisms was reported at a certain concentration in Japan (Hatakeyama 1989). Potential environmental risks of zinc in surface water were pointed out and wastewater effluent was considered as one of the pathways of zinc to surface water in Europe (Bodar et al 2005).…”
Section: Introduction and Purposementioning
confidence: 99%